Fatigue of the glue - spot welded and rivet joints, treated by anticorrosion protective coating - Карускевич, М.В.; Карускевич, О.М.; Маслак, Т.П. (Proceedings of National Aviation University (archive), 2005)
Research results of the influence of film forming inhibitor oil composition on fatigue of aircraft An-24 and An-26 structure elements are presented. The diagnostic methods for early fatigue stage, based on quantitative estimation of surface deformation relief under cyclic loading is approbated. Recommendations on practical use of film forming inhibitor oil composition for anticorrosion protection of An-24 and An-26 aircraft are developed.